Lead acetate ecotoxicity in tropical soils - Alexandrino, R. C. S. (2021)
Lead acetate (AcPb) is an important raw material used in chemical industries worldwide. The potential toxicity of AcPb is generally attributed to the presence of Pb. However, the effect of AcPb on the environment as a whole is still poorly known. This study aimed to evaluate AcPb toxicity on three standard species of soil invertebrates and two plant species using ecotoxicology tests. Three tropical soils (Oxisol, Inceptisol, and Tropical Artificial Soil (TAS)) were contaminated with different concentrations of AcPb and one dose of K-acetate (positive control). These soils were used in tests with Eisenia andrei (earthworm), Folsomia candida (springtail), Enchytraeus crypticus (enchytraeid), Zea mays (maize), and Phaseolus vulgaris (common bean). Dose-response curves obtained in the laboratory tests were used to estimate the EC50 values for each species. Among invertebrates, the highest sensitivity to AcPb was observed for E. crypticus in the TAS (EC50 = 29.8 mg AcPb kg-1), whereas for E. andrei and F. candida the highest sensitivity was observed in the Oxisol (EC50 = 141.9 and 1835 mg AcPb kg-1, respectively). Folsomia candida was the least sensitive invertebrate species to AcPb in all soils. Among plant species, Z. mays was less sensitive (EC50 = 1527.5 mg AcPb kg-1) than P. vulgaris (EC50 = 560.5 mg AcPb kg-1) in the Oxisol. The present study evidenced that the toxicity of AcPb should not be attributed uniquely to the presence of Pb, as the treatment containing uniquely Ac provoked the same toxicity as the highest dose of AcPb.